The risk of Sukuk (Islamic bonds) and conventional bonds: comparative study - Barqawi, Omamah Ameen (Journal of Economic, Administrative and Legal Sciences, 2018)
The current study aimed to investigate one of the key products in the Islamic capital market, which is the asset-backed Islamic bonds, known as (sukuk), the study aims to investigate the risk of sukuk and compare and contrast (sukuk) to conventional bond, moreover, the study attempts to discuss factors that affect the price of (sukuk) and conventional bond and to recommend a pricing model that can be applied to (sukuk). The study applied a mixture between quantitative and qualitative method. The qualitative research is covered in Reviewing Literature related to (sukuk) and bonds and the quantitative method is used to explain the models of conventional bonds and using the same model for Islamic bonds (sukuk) by comparing the coupon rate, duration and convexity of conventional bonds and Islamic bonds using suitable equation. The data gathered for the current research is obtained from Dow Jones (sukuk) Index in a number of different regions such as Malaysia, Saudi Arabia, Kuwait, Qatar, Bahrain, the UAE and Pakistan. The findings showed that the calculated (sukuk) prices is shown to be different from the Dow Jones, and it represents a more accurate representation of the market price of the (sukuk) bonds, given that investors use the rate of return of 3.75%. The conventional bonds pricing model can be used to price (sukuk), simply by changing the coupon rate with profit rate. They are also generally exposed to the same risk, however (sukuk) are exposed to more risks such as shariah compliance risk and regulation risk. Despite the additional risks, (sukuk) has slightly lower risk than conventional bonds due to the principle of profit and loss sharing and the existence of the assets.
Keywords: sukuk; Rate and Payment; Return; Bonds; Cash Flow; Coupon Rate; Pricing